Impact creation approaches of community-based enterprises: A configurational analysis of enabling conditions - Mitzinneck, Björn C.; Coenen, Jana; Noseleit, Florian; Rupietta, Christian (Journal of Business Venturing, 2024)
This study investigates which local conditions enable community-based enterprises (CBEs) to create impact. Advancing our limited understanding of the various contexts that enable CBEs to tackle societal issues locally, we investigate supportive conditions across 77 CBEs driving the energy transition in their geographic community. Through qualitative comparative analysis, we identify four condition configurations for CBE impact creation. Across these configurations, we reveal transferable mechanisms helping CBEs to engage community members ( Opportunity- and Community-anchoring ) and handle the absence of a supportive condition (Circumventing and Compensating). Our study suggests how CBEs can combine these mechanisms to create impact in varied local contexts. • Our study informs how community-based enterprises (CBEs) can generate local impact based on available local conditions. • No single condition is necessary or (by itself) sufficient for impact creation. • CBEs can build upon various condition combinations that can help deal with a barrier (lacking condition). • CBEs enhance resourcefulness by passing barriers with Circumventing and overcoming them with Compensating strategies. • CBEs engage communities by highlighting benefits ( Opportunity-anchoring ) or emphasizing relationships ( Community-anchoring ).